The Impact of the Covid-19 Pandemic on Corporate Performance and Cash Dividend Distribution in China's Manufacturing Industry - Danni, Wang; Sang, Lim Thien; Guangmei, Lei (UI Scholars Hub, 2025)
As an unprecedented global public health emergency with rapid spread and challenging prevention and control measures, the COVID-19 pandemic has profoundly impacted corporate performance worldwide. Notably, the manufacturing industry in China has been severely impacted. To comprehensively understand the influence of significant public health incidents on enterprises and mitigate the epidemic's repercussions, the unbalanced panel data of China's A-share listed manufacturing enterprises from 2018 to 2023 was analyzed by regression analysis. The findings demonstrate that the COVID-19 outbreak has diminished these enterprises' financial and market performance. Moreover, companies with higher cash dividends and more excellent stability exhibit superior future performance in the face of the impact. This finding implies that cash dividends are pivotal in augmenting corporate performance during uncertain periods following unexpected adverse events, suggesting potential adjustments and optimizations to the development strategy and dividend payment policy.